2011
DOI: 10.1128/iai.00629-10
|View full text |Cite
|
Sign up to set email alerts
|

Role of Tannerella forsythia NanH Sialidase in Epithelial Cell Attachment

Abstract: Tannerella forsythia is a Gram-negative oral anaerobe which contributes to the development of periodontitis, an inflammatory disease of the tooth-supporting tissues leading to tooth loss. The mechanisms by which this bacterium colonizes the oral cavity are poorly understood. The bacterium has been shown to express two distinct sialidases, namely, SiaHI and NanH, with the latter being the major sialidase. Bacterial sialidases can play roles in pathogenesis by cleaving sialic acids on host glycoproteins, destroy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
74
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(80 citation statements)
references
References 43 publications
4
74
0
2
Order By: Relevance
“…forsythia has been detected intra-cellularly in buccal and crevicular epithelium of patients with periodontitis (Rudney et al, 2005) and has been shown to invade epithelial cells in vitro (Inagaki et al, 2006;Mishima and Sharma, 2011). We observed over-representation in periodontitis of a homolog of the cell-surface-associated protein sialidase NanH (locus VBITanFor42681_2003) required for attachment to epithelial cells (Honma et al, 2011).…”
Section: Discussionmentioning
confidence: 70%
“…forsythia has been detected intra-cellularly in buccal and crevicular epithelium of patients with periodontitis (Rudney et al, 2005) and has been shown to invade epithelial cells in vitro (Inagaki et al, 2006;Mishima and Sharma, 2011). We observed over-representation in periodontitis of a homolog of the cell-surface-associated protein sialidase NanH (locus VBITanFor42681_2003) required for attachment to epithelial cells (Honma et al, 2011).…”
Section: Discussionmentioning
confidence: 70%
“…While a number of periodontal bacteria are known to exploit host sialylated glycoproteins as a nutrient source, sialidase activity also plays an important role in their pathogenicity. Sialidase treatment of immunoglobulins can make them more susceptible to proteolytic degradation; sialidases may also reveal cryptic receptors and/or adhesion sites for bacterial binding/interaction and hence tissue and host tropism (5,19). Our studies have identified three sialidase-related genes in P. gingivalis which have shown a specific pattern of clustering with other related genes from the bacteria.…”
Section: Discussionmentioning
confidence: 85%
“…Neuraminidase activity has also been detected in several oral bacteria, such as Tannerella forsythia and Porphyromonas gingivalis (44,66). T. forsythia possesses two neuraminidases, and one of them (NanH) is associated with bacterial colonization and invasion (28,51).…”
mentioning
confidence: 99%